Secular Changes of Adiposity and Motor Development in Czech Preschool Children: Lifestyle Changes in Fifty-Five Year Retrospective Study - Petr Sedlak (BioMed Research International, 2015)
Secular trends of adiposity and motor development in preschool children since the fifties of the last century up to the beginning of this millennium were analyzed so as to reveal possible changes due to continuously differentiating lifestyle. In preschool children (n=3678) height, weight, skinfold thickness over triceps, subscapular, and suprailiac were measured by Harpenden caliper in 1957, 1977, 1980, 1985, 1990, and 2012. Simultaneously, motor performance was tested by evaluating the achievements in broad jump and throwing a ball, as a marker of adaptation to changing level of physical activity, free games, and exercise. Along the period of five decades the values of skinfold thickness increased significantly until 2012, mainly on the trunk. Simultaneously, the level of motor performance significantly decreased. Modifications of the way of life during the mentioned five decades characterized by sedentarism and inadequate food intake as related to energy output influenced negatively both adiposity and motor performance already in preschool children. Mostly increased deposition of fat on the trunk which is considered as a marker of possible development of metabolic syndrome was apparent already in preschool age, indicating the importance of early intervention concerning also physical activity and availability for exercise since early life.